Timing is everything: Within-plant flowering phenology impacts fruit production in the Arctic-Alpine cushion plant Silene acaulis (L.) Jacq. - Ween, Rebekka Eriksen (UiT Norges arktiske universitet, 2022)
Timing is everything for Arctic flowering plants. Early flowers might be destroyed by frost, while late flowers have less time and resources to mature fruit. With climate change, Arctic flowering phenology is shifting. Yet for many species, phenology studies only encompass the onset of flowering and lack baseline data on within-plant flowering times. I used the gynodioecious cushion plant Silene acaulis (L.) Jacq. to investigate how within-plant flowering phenology impacts fruit production in one growing season. In 2019, time-lapse cameras were used to daily observe flowers within two populations in the Low-Arctic (Narsarsuaq, Greenland in the Low-Arctic/Sub-Arctic transition zone; 7851 flowers, 21 plants) and the High-Arctic (Bjørndalen, Svalbard; 1587 flowers, 11 plants). Plants flowered for approximately three weeks, with a positively skewed peak floral display. In the LowArctic site, most investigated individuals were females dependent on pollinator visits for fruit production. Within these Low-Arctic females, flowers blooming during peak floral display had a higher probability of fruit set than flowers blooming outside peak floral display. In addition, flowers blooming before peak flowering were more likely to produce fruit than flowers blooming after peak flowering, both at the individual level and between individuals within the whole population. Hermaphrodites, however, can self-pollinate, and preliminary results indicate higher fruit set outside peak flowering within individuals and populations. In contrast to the Low-Arctic site, all plants in the High-Arctic site were females and a frost event occurred during flowering. Despite the frost event, females in the High-Arctic site had twice as high fruits per flower proportions as females in the Low-Arctic site. For flowers not exposed to frost, similarly to the Low-Arctic site, flowers blooming during peak floral display were more likely to produce fruit than flowers blooming outside peak floral display. Also similar to the Low-Arctic site, early flowers, ...